Climate smart agricultural practices improve soil quality through organic carbon enrichment and lower greenhouse gas emissions in farms of bread bowl of India - Datta, Ashim; Nayak, Dali; Smith, J.U.; Sharma, Parbodh Chander; Jat, Hanuman Sahay; Yadav, A.K.; Jat, Mangi Lal (Commonwealth Scientific and Industrial Research Organisation, 2022)
Context: Climate change can impact greatly on poorer and vulnerable communities, increasing the risk of natural disasters, and affecting agricultural production. Aims: This study aims to explore the potential impacts of climate smart agricultural practices (CSAP) on working farms in Karnal, Haryana, India. Methods: Practices studied included zero tillage, crop residue retention and crop diversification. We surveyed soil physical and chemical properties and greenhouse gas emissions on farms managed by either CSAP or conventional agriculture. Soil samples were collected at 0–20 cm depth under wheat grown in the winter season. Key results: Of the 70 farmers surveyed, 22 followed CSAP while 48 farmers used conventional practices. Soil pH was lower (7.76) for CSAP farms compared to conventional practices (7.99). Soil carbon was also higher (0.19% compared to 0.13%), as were total organic carbon stock (32.03 Mg ha−1 compared to 25.26 Mg ha−1) and total carbon (0.24% compared to 0.16%). Significant interactions between farming type, pH and organic carbon, gravimetric and volumetric water content were observed. Conservation agriculture registered ∼31% higher soil quality index over conventional practice. Higher wheat grain yield (5.99 t ha−1) was observed under conservation agriculture over conventional (5.49 t ha−1). Greenhouse gas emissions were also ∼63% higher in conventional practices compared to CSAP. Conclusions: CSAP can improve soil properties through enrichment in soil organic carbon at the same time as reducing emissions of greenhouse gases. Implications: CSAP provide an alternative to conventional agriculture practices in north-west India, irrespective of farm type and size. CSAP not only improve soil carbon pools, but also improve the overall quality of the soil.